Characterization of Vibrio vulnificus Isolated from the Coastal Areas in the Eastern Province of Saudi Arabia - Zainab Alsalem; Nasreldin Elhadi; Mohammed Aljeldah; Faisal Alzahrani; Mitsuaki Nishibuchi (Journal of Pure and Applied Microbiology, 2018)
Vibrio vulnificus is a Gram-negative, halophilic bacterium that mainly inhabits marine environments. It is responsible for causing gastroenteritis upon consuming contaminated seafood or exposure of an open wound to seawater. In addition, it has the ability to cause wound infection and septicaemia. It is also known to be an opportunistic organism that targets immunocompromised patients and those with liver disease. In the present study, 362 seawater samples were collected from 17 different locations along the coastal areas of the Eastern Province of Saudi Arabia and were analyzed for the presence of V. vulnificus. There were 65 (17.95%) positive samples and 234 isolates of V. vulnificus. All positive isolates were tested for pathogenicity using PCR to detect the hemolysin-cytolysin (vvhA) gene, which was found in 52 (22%) of the isolates. The antibiotic susceptibility test indicated high resistance to ampicillin (96%), cephalothin (73%), rifampicin (63%), and amoxicillin-clavulanic acid (56%). The MAR index was calculated for all antibiotics and revealed significant values (>0.2) for 34.6% of V. vulnificus isolates. Isolates positive for the vvhA gene were genotyped by using Enterobacterial Repetitive Intergenic Consensus (ERIC-PCR) DNA fingerprinting. ERIC-PCR fingerprints of 52 isolates of V. vulnificus generated high similarity scores ranging from 85 to 100%, indicating significant genetic relatedness between the isolates. This study is the first to report the isolation of V. vulnificus positive for the vvhA gene from the coastal water in the Eastern Province of Saudi Arabia.